Peran Telemedicine dalam Meningkatkan Akses Layanan Kesehatan di Era Globalisasi - Hasan Basri; Ahmad Idris (Lembaga Penelitian dan Pendidikan, 2025)
The development of information and communication technology in the era of globalization has driven significant transformation in the healthcare sector, particularly through the adoption of telemedicine. This study aims to analyze the role of telemedicine in improving access to healthcare services, especially in areas with limited facilities and medical personnel. The research method employed is a literature review with a qualitative approach, examining various national and international sources related to the effectiveness, challenges, and opportunities of telemedicine implementation. The findings indicate that telemedicine can expand service coverage, accelerate the diagnostic process, improve cost efficiency, and provide convenience for remote consultations. However, challenges remain, including limited digital infrastructure, low technological literacy among communities, and regulatory frameworks that require further strengthening. In conclusion, telemedicine plays a strategic role in ensuring equitable access to healthcare services in the globalization era, provided that it is supported by adaptive policies, robust digital infrastructure, and improved digital health literacy among the population.